Analytical Study on Time-Dependent Stiffness of Stud Shear Connectors - Liu, Rong; Sun, Xinyang; Ye, Hengda; Liu, Yuqing (Frontiers in Mechanical Engineering, 2022)
Concrete creep weakens the spring stiffness of stud shear connectors (SSCs) and increases the long-term deflection of long-span composite beams. The time-dependent properties of SSC are of great importance for the long-term evaluation of composite steel construction. This paper proposes the time-dependent stiffness (TDS) method based on the analytical solution of the beam on a viscoelastic foundation to simulate the SSC under the sustained push-out load. TDS method combines beam theory and the viscoelastic property of hardened concrete. The long-term slip of SSC is predicted by hand calculation of the explicitly expressed governing equation, and it is close to the refined finite element analysis (FEA) results. The constants and parameters used to determine TDS seem to be insensitive regarding geometric and material variation. TDS may provide a simplified method to incorporate the time-dependent partial interaction into complex composite structures by saving the consumption of computer storage and advanced modeling time which are usually required in the refined modeling at the steel-concrete interface, especially when the long-term properties of concrete are of interest.